The Impact of Religiosity, Discounts, and Cashback Toward Impulsive Purchases among Gen Z Consumers on Tokopedia: An Islamic Perspective - Sukarno, Hari; Cholifah, Umi; Azzam, Naufal; Diniyya, Aulia Arifatu (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
The merger of Tokopedia has resulted in the introduction of new sales promotions and discounted prices, which act as triggers for impulsive purchases among Muslim consumers on the platform. This study aims to examine the impact of religiosity, discounts, and cashback on impulsive purchases on Tokopedia, with a specific focus on the Islamic perspective. The research approach method used in this study is a quantitative approach with an associative design, conducted as a field study on the Muslim community making purchases on Tokopedia. The sampling technique utilized the Hair formula, and 138 Muslim respondents were selected through Purposive Sampling in Jember Regency. Data collection was conducted through a questionnaire. The data analysis techniques employed included multiple regression analysis, t-test, and F-test. The research findings indicate that religiosity has a significant negative influence, while discounts and cashback have significant positive influences on impulsive purchases among Muslim communities in Jember Regency. From an Islamic standpoint, Muslim consumers in Jember Regency display high levels of religiosity and adopt a rationalist approach when making product decisions. The implication of the study shows that religiosity has a significant negative impact, while discounts and cashback have significant positive impacts on impulsive purchases among the Muslim community in Jember Regency. This indicates that these factors can influence the impulsive buying behavior of Muslim consumers on the Tokopedia platform.